REVERENCE OF BOOKS IN ARMENIAN FOLK CHRISTIANITY - Krukova, Natal'a Vladislavovna (History, Archeology and Ethnography of the Caucasus, 2024)
In certain regions of Armenia, there exists a unique cult of shrine books. These ancient books, often including early printed and handwritten copies, become objects of veneration. When such a book is kept in a family, it commonly becomes known as tan surb, or “saint of the house.” A sanctuary is built for the book, it has a dedicated keeper, and pilgrimages are made to it. Various taboos and prophetic dreams are associated with these books, to which people pray and make sacrifices. Most often, these revered books are the Gospels or works by Grigor Narekatsi, but they also include khmayils – scrolls with magical content. This research aims to identify and describe the main types and components of community and home rural sanctuaries, known as surbs. The cult of shrine books is examined through the broader context of the general cult of rural surbs, characteristic of this Armenian region. The study employed participant observation and interviews with local residents – venerators of rural surbs in the Aparan region of the Republic of Armenia – between 2016 and 2023. The findings reveal that home and community shrines in this region often include ancient books of religious content as well as khmayil scrolls. Based on an analysis of the collected material and existing scientific literature, this article describes contemporary ideas and practices related to the veneration of these shrines and compares them with the general cult of rural surbs in the region.
Keywords: Armenians; Armenia; folk Christianity; vernacular; Gospel; surb; khmayil; tan surb; shrine; saint